(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Orbital fractures are an urgent issue in ophthalmological as well as maxillofacial/ plastic surgery practice. The management of orbital fractures is often challenging due to the impact that they can have not only on the cosmetic appearance of the treated area but also on vision. Here we review the major aspects of current reconstructive orbital surgery. This review will primarily focus on the surgical approaches to the fracture site and types of implants available for restoration of the integrity of orbital walls. Their most significant advantages and disadvantages, as well as results of studies on the efficacy of various types of implants, will be reviewed.